Comparison of arsenic co-precipitation and adsorption by iron minerals and the mechanism of arsenic natural attenuation in a mine stream. (1st December 2016) - Park, Jin Hee; Han, Young-Soo; Ahn, Joo Sung
Abstract: Mine stream precipitate collected from Ilkwang mine, Korea, contained high concentrations of arsenic (As), while water collected from the same site had negligible As concentrations, indicating natural attenuation of As occurred in the mine stream. The mechanism of attenuation was explained by comparison of X-ray absorption near edge structure (XANES) of As(V) co-precipitated with or adsorbed to iron (Fe) minerals in mine precipitates. Arsenic in the mine precipitate was present as As(V) and schwertmannite was the main Fe mineral. Arsenic co-precipitation with schwertmannite was the major mechanism of As removal in the mine stream, followed by As adsorption by goethite and As co-precipitation with ferrihydrite. Schwertmannite and ferrihydrite were formed in acid mine drainage and As was incorporated in their structure during formation. Additionally, schwertmannite and ferrihydrite may transform to goethite with As adsorbed onto the goethite surface. Based on the results of batch experiments of As co-precipitation and adsorption, co-precipitation of As with ferrihydrite and schwertmannite was the most effective As sequestration mechanism in the removal of As(V) from acid mine drainage. Graphical abstract: Highlights: Ferrihydrite and schwertmannite removed more As by co-precipitation than adsorption. Schwertmannite, ferrihydrite and goethite were formed in acid mine drainage. Arsenic was removed through co-precipitation of As(V) with schwertmannite in mine. Schwertmannite was transformed to goethite and As(V) adsorbed onto the goethite. Natural attenuation of As occurs in environments where Fe minerals are formed.